Economía circular y su relación con el medio ambiente en el Gobierno Autónomo Descentralizado Municipal del cantón Tosagua período 2023 - Tuárez Zambrano, Gema Yamileth (2025)
This research was conducted to strengthen the efforts of the GADM in Tosagua canton in improving its relationship with the environment by determining the level of importance given to the practice of circular economy as a foundation for environmental support. Consequently, the methodology employed was both bibliographic and field-based, carried out in three phases to facilitate the achievement of the established objectives. Initially, a bibliographic and legal review of the study variables was conducted, demonstrating that this practice is essential in Tosagua canton for contributing to environmental well-being through compliance with existing laws. However, to better understand this relationship, data collection techniques such as interviews and surveys were applied, targeting the Environmental Unit Specialist of the entity and the general public. The findings revealed that the circular economy is crucial for the proper use of natural resources. Despite this, the canton faces multiple challenges, particularly the lack of measures for soil protection and water conservation. Additionally, a lack of education on local environmental issues fosters a perception of inefficiency in resource management. Therefore, a pilot plan was developed, outlining specific actions to address the identified problems.